THE IMPROVING STUDENTS' SPEAKING SKILL TROUGH DRAMA AT THE SECOND GRADE OF SMAN 8 BULUKUMBA - Gita Hervina, A; Nur Ina Syam; Mutmainnah Marzuki (Jurnal Pendidikan Sang Surya, 2023)
The objective of the research to find out if there is an increase in speaking skill after learn with using drama at the second grade students’ of SMAN 8 Bulukumba.The researcher applied pre-experimental with pre-test and post-test design. The population of this research was taken by Purposive sampling technique from the second grade of SMAN 8 Bulukumba in academic year 2022/2023. This sample consist of 25 students. In collecting data, the researcher gave a speaking test there was pre-test and post-test, while to analyze the data the researcher used t-test.The researcher concludes that drama was effective to improve the students' speaking skills in terms of comprehension. vocabulary, pronunciation, grammar, andfluency. It was proven by the students' improvement in the student's comprehension of speaking was (85.07%), vocabulary (82.97%), pronunciation (40.68%), grammar (40.18%), and the students' fluency was (68%) It can be concluded that the students' comprehension, vocabulary, pronunciation, grammar, and fluency in speaking at the second grade of SMAN 8 Bulukumba improved after applying a drama Based on hypothesis testing, the null hypothesis (H0) was rejected whereas the alternative hypothesis (H1) was accepted It was proven by the value of the 1- test in comprehension (8.75), vocabulary (2.35), Pronunciation (7.85), grammar (11.66), and the value of the t-test in fluency (7.5) which were greater than the value of the t-table (1.711). In other words, the use drama was effective to improve the students' speaking skills.